Genetic and Molecular Regulation of Seed Storage Proteins (SSPs) to Improve Protein Nutritional Value of Oilseed Rape (Brassica napus L.) Seeds - Gacek, Katarzyna; Bartkowiak-Broda, Iwona; Batley, Jacqueline (Frontiers in Plant Science, 2018)
The world-wide demand for additional protein sources for human nutrition and animal feed keeps rising due to the rapidly growing world population. Oilseed rape (Brassica napus) is the second most important oil producing crop and the by-product of the oil production is a protein rich meal. The protein in rapeseed meal finds its application in animal feed and various industrial purposes, but its improvement is of great interest, especially for non-ruminants and poultry feed. To be able to manipulate the quality and quantity of seed protein in oilseed rape, understanding the genetic architecture of seed storage protein (SSP) synthesis and accumulation in this crop species is of great interest. For this, application of modern molecular breeding tools such as whole genome sequencing, genotyping, association mapping and genome editing methods implemented in oilseed rape seed protein improvement would be of great interest. This review examines current knowledge and opportunities to manipulate SSPs in oilseed rape to improve its quality, quantity and digestibility.